The Health Costs and Diseases in Medical Services Insurance Organization, Tehran Province, 1386 (2008) - Ali Shojaei; Ahmad Ali Akbari Kamrani; Reza Fadaye vatan; Mojtaba Azimian; Shahram Ghafari; Mohammad Reza Jamali (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: The current research in addition to study of the diseases in the elders, surveys the health costs of these diseases. Methods & Materials: Study of the cost information and related diseases in (MSIO)- Medical Services Insurance Organization, Tehran province, surveys costs and Medical Services of this group on 183093 hospitalized files. Results: 31% of hospital`s referrals and 37% of inpatient costs related to elders and display the expensive Services of this group of the Insured. The mean costs of every hospitalization in elderly groups were 4634384 rials, which was more than total mean costs, from all groups. Diagnostic code I27 (other cardio-vascular diseases), I20 (Angina pectoris), H25 (cataract), I25 (chronic IHD), I50 (heart failure), devote first to fifth grade of the prevalent Diagnosis cods (ICD) in the aged group older than 60 and displays the most prevalence of the cardio-vascular system diseases in the elders. The most common surgical Code (California code) in elderly (above 60 yrs.) was related to Coronary Angioplasty, with its mean cost of 9116371 rials. And then was Cataract. 15% of the Global files are related to the elders which is equal to 23% of the charges of these files in this group of the elders. Extraction of Lens (Intra-capsular and extra-capsular) Lens Insertion (57 code) One-lateral Inguinal Hernia with or without excision of Hydrocele or Spermatocele except Incarcerated Inguinal Hernia (Global code 28), cholecystectomy with or without cholangiography or exploration of Biliary ducts (Global code 27) from first to third grade of the prevalent Global surgeries of the elders. Statistical test displays the Pierson coherent between the age and residence period and paid costs, There is a little positive coherent between the age and residence period in hospital and paid costs. Conclusion: These reviews show the results of the current study (the prevalent in-patient causes) are adapted to the performed studies in this field and cardio-vascular diseases are the most prevalent diseases of the elders with the most health costs.